Concentration of Migrant Students in Santiago (Chile) and Institutional Discourses: Differences with the Spanish Case; [Concentración de Alumnado Migrante en Santiago (Chile) y Discursos Institucionales: Diferencias Con el Caso Español] - Cordoba-Calquin, C (Universidad Autonoma de Madrid, 2023)
In the context of a growing increase in the migrant population in Chile, we analyze the uneven distribution and problematic incorporation of these students in schools of Santiago, where the segregation reaches its greatest magnitude. Through a mixed methods analysis -quantitative, geographical and qualitative- we present a picture of the school concentration in “Greater Santiago” calculated through indicators of segregation, and a discursive analysis of heads of high-concentration schools (CAC) about the reasons for this concentration. Finally, we compare the results with a similar case study carried out in Spain. The results point, firstly, to very high and heterogeneous levels of segregation in the Chilean capital; secondly, to an unequal location of schools in the territory, which draws and reproduces unequal levels of school concentration by district; thirdly, there are CACs in charge of the schooling of migrant students that reproduce dynamics of institutionalized school concentration. The discussion of comparative results suggests differences in the conception of school concentration, more standardized, functional and accepted in the Chilean case, probably as a result of more deeply rooted educational market logics. © 2023 Universidad Autonoma de Madrid. All rights reserved.